Are NLR Rate and MPV Values Useful in Predicting Malignancy in Follicular Neoplasia, Atypia of Undetermined Significance and Suspicious Cytology? - Murat Doğan; Aykut Soyder (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:Neutrophil-to-lymphocyte ratio (NLR), an indicator of systemic inflammation, and mean platelet volume (MPV) have been found to be associated with carcinogenesis in many studies. The aim of this study was to investigate the predictive values of these two parameters in detecting thyroid malignancy.Materials and Methods:Patients who were reported to have atypia of undetermined significance, follicular neoplasia and suspected cytology as a result of thyroid fine needle aspiration biopsy (FNAB) in a tertiary health care facility between January 2010 and December 2017 and who had undergone total thyroidectomy or hemithyroidectomy due to this were evaluated. The data of 225 patients were retrospectively reviewed, and 144 patients (29 females/115 males) were included in the study.Results:When patients found to be malignant and benign as a result of the pathology results were compared, preoperative NLR values were detected to be statistically significant in malignant patients (p=0.002). Preoperative MPV values were found to be statistically insignificant. When compared in terms of FNAB groups, we found a significance only in suspicious cytology (p=0.001) but found no significance in the other groups.Conclusion:NLR may be useful in the differentiation of benign and malignant diseases but still cannot provide clear data for predicting malignancy between FNAB groups.